PERATURAN HUKUM PERDATA NASIONAL DI ERA DIGITAL HAMBATAN DAN KESEMPATAN DALAM MELINDUNGI DATA PRIBADI - UTIARAHMAN, NURAISAH MASITA (Ganec Swara, 2025)
The digital era has had a significant impact on various aspects of life, including from the perspective of national civil law. The use of digital technology and the internet has given rise to various new sectors such as e-commerce, e-education, and e-health, which have encouraged the creation of new challenges in the civil law system, especially regarding the protection of personal data, electronic contracts, and online business transactions. In the context of civil law, the protection of personal rights and personal data is an important issue, considering the increasingly widespread collection and use of personal data. Apart from that, the development of e-commerce and e-government requires regulations that are able to protect consumer rights, as well as ensure the security of data and transactions in the digital world. This article analyzes the challenges and opportunities that arise in protecting personal data in the digital era as well as the importance of adaptive regulatory updates to face rapid technological advances. This research uses a normative approach with descriptive analysis. Researchers focus on national civil regulations relevant to personal data protection in the digital era, including the Personal Data Protection Law (UU PDP). The goal to be achieved is in order to know, understand; What is the Role of National Civil Law Regulations in the Digital Era? Barriers and Opportunities in Protecting Personal Data. The results of this research are that this research contributes to the understanding of personal data protection regulations in Indonesia and how civil law can adapt in the context of the digital era. The results of this research also enrich legal literature related to legal challenges in the digital era and provide new views regarding the implementation of regulations in the technology sector.